Study of Perceived Value Instrument in Thesis Writing Using CFA - Ilham Phalosa Reswara; Whisnu Yudiana; Surya Cahyadi (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2021)
Perceived value had a major role in an academic activity, including in thesis writing. Unfortunately, there was no study that validated perceived value inventory in the thesis writing setting using empirical evaluation. Thesis writing has specific characteristics that make it unique compared to the general academic activity. Therefore, specific measurement is needed to accurately measure it. The present study aimed to validate the perceived value scale using construct validity approach. The research participants (N = 219) were university students from several faculties. Confirmatory Factor Analysis (CFA) was used to validate the construct. Reliability was also estimated in this study. The result showed that the modified model was fit. The goodness of fit was estimated using Comparative Fit Index (CFI), Root Mean Square Error of Approximation (RMSEA), Goodness-of-Fit Index (GFI), Normed Fit Index (NFI), and Non-Normed Fit Index (NNFI). The factor loading of each item was in range of .58 - .87, the Construct Reliability (CR) of each dimension were .81 and .77, and the Average Variance Extracted (AVE) of each dimension were .52 and .54. The reliability of the whole construct and its factors were satisfying (>.70). This result indicated that this scale was satisfying in overall structure and its convergence.